Mediators: accreditation and training requirements - Lau, William KH; Ali Mohamed, Ashgar Ali (The Malaysian Current Law Journal Sdn Bhd, 2020)
This chapter discusses the accreditation requirements of mediators with reference to selected jurisdiction. The reasons and the benefits for accreditation, who should regulate and the qualifications required for accreditation among others are also addressed in this chapter. At this juncture, it is worth noting that the Mediation Act 2012 provides that only a person who possesses the relevant qualifications, knowledge or experience in mediation through training or formal tertiary education or satisfies the requirements of an organisation which provides mediation services, can be appointed as a mediator under the Act.